LOCAL WISDOM OF TRADITIONAL MEDICINE IN BATAK TOBA - Juni Agus Simaremare (Linguistik, Terjemahan, Sastra (LINGTERSA), 2021)
The objectives of this research are (1) To find traditional healing traditions in the Batak Toba community (2) to find the local wisdom of traditional medicine in the Batak Toba community. This research is a qualitative descriptive study. Data collection techniques in this study are interview and observation techniques. The theory used to study traditional medicine traditions in the Toba Batak community is an anthropolinguistic theory, namely performance, indexicality, participation by applying three parameters, namely (1) Interconnection, (2) Value), and (3) Continuity. The results of this study indicate that the traditional healing traditions of the Toba Batak community come from natural products in the form of roots, fruits, gums, sweet potatoes, bark, wood, animals, metals, oil, leaves, and other natural ingredients. Based on the method of the treatment process, various methods were found, namely roasting, boiling, milling, twisting, while the community medicinal process was rubbed, drunk, sprayed and bathed. The local wisdom of traditional medicine in the Toba Batak community is the achievement of harmony. The local wisdom of the welfare felt by the community is reflected in treatment, namely helping each other between communities so that the value of welfare between humans and healthy communities is created by utilizing the surrounding environment. The people's habit of sharing and helping to heal each other reflects a religious foundation. The resilience of this religious value is reflected in the belief of society that all-natural products they use in medicine come from Almighty God.